Enhancing MSME Performance and Local Tourism Development in Pematang Johar through Digital Marketing Strategies - Haryadi Haryadi; Ahmad Hidayat; Miftah El Fikri; Shintami Oktavia; Muhammad Hafiz Abd Rashid; Ridho Syafrizal; Meriani Gunawan (Eastasouth Journal of Positive Community Services, 2025)
The International Community Service conducted in Pematang Johar Village, Deli Serdang Regency, aims to empower local MSMEs and promote sustainable tourism through digital marketing innovation. Despite its rich tourism potential and strategic location, most local entrepreneurs still rely on conventional marketing methods with limited digital engagement. This activity focused on strengthening digital literacy and marketing competencies among MSMEs to support local tourism development. The program adopted the Service-Learning method involving workshops, mentoring, and hands-on practice in social media marketing, content creation, and e-commerce utilization. The results revealed a significant increase in participants’ understanding of digital promotion and brand development, reflected in improved online visibility and sales performance. This initiative demonstrates how digital empowerment can serve as a catalyst for inclusive rural tourism growth and economic sustainability in Pematang Johar.